Метафорическое использование названий животных и птиц в художественных текстах Т.Каипбергенова (SCIENCE and SOCIETY, 2023)
This article discusses metaphor as a figurative means of the literary text of the writer T. Kaipbergenov. The study was carried out on the material of the novel by T. Kaipbergenov "Maman biy әpsanasy" ("The Tale of Maman biy").